Prostate cancer in primary care: mitigation strategies through health education (Research, Society and Development, 2020)
Prostate cancer emerges as one of the most fatal for the male audience, and can significantly interfere with their quality of life when not previously diagnosed, being often lethal, which emphasizes the importance of working on the topic within the health network. This work aimed to report a health education action experienced by nurses and nursing students about the awareness of the male public about the prevention of prostate cancer, through an educational action alluding to the blue November in a basic peripheral unit in the city of Belém- PAN. This study qualifies as descriptive, of the experience report type, based on the arch of Charles Maguerez. From the main results achieved with the implementation of the proposed interventions, it was observed that the educational action played a relevant role in the lives of the participants, since it served as a consolidating mechanism of the health principles, promoting an effective self-management of health and empowerment of the target audience about the main aspects that permeate prostate cancer.